Swelling and Contraction of Potato Mitochondria - Jung, Dennis W. (1979)
Mitochondria isolated from potato tubers fail to undergo passive osmotic swelling when suspended in isotonic Na(+) acetate or phosphate, in NaCl following addition of tripropyltin, or in Na(+) nitrate following addition of an uncoupler. Swelling under each of these conditions in mitochondria from other sources has been attributed to the inward movement of Na(+) on an endogenous Na(+)/H(+) exchanger. Such a monovalent cation/H(+) exchanger has also been implicated in respiration-dependent cation extrusion and contraction of swollen mitochondria. Potato mitochondria swollen in chloride and nitrate salts extrude ions and contract when respiration is initiated. The contraction reaction is slower and less efficient than that in beef heart mitochondria, but like the latter, is sensitive to uncouplers and stimulated by nigericin, butacaine, and Mg(2+). These comparative studies suggest that a cation(+)/H(+) exchanger is present in potato tuber mitochondria, but that it functions exclusively as a cation-extruding mechanism. They further suggest that cation(+)/H(+) exchange activity is not identical in mitochondria from different sources and that these exchange components may have a directionality and regulatory features which differ with the metabolic needs of the source tissue.